2020
DOI: 10.36560/13520201031
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilizations via leaf on soybean stages and nitrogen released on yield of off season maize

Abstract: Fiorini et al. Nitrogen fertilizations via leaf on soybean stages and nitrogen released on yield of off season maize 33

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Martins, et al [29], working with coated MAP, observed that corn grain yield increased with increasing doses of P 2 O 5 up to about 132 kg ha −1 , regardless of whether or not MAP was coated with polymers. In terms of grain yield, Fiorini et al [30] did not detect responses in grain yield using policote-coated MAP compared with conventional MAP and suggested that this is due to the phosphorus content in the soil being very close to the value considered optimal in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Martins, et al [29], working with coated MAP, observed that corn grain yield increased with increasing doses of P 2 O 5 up to about 132 kg ha −1 , regardless of whether or not MAP was coated with polymers. In terms of grain yield, Fiorini et al [30] did not detect responses in grain yield using policote-coated MAP compared with conventional MAP and suggested that this is due to the phosphorus content in the soil being very close to the value considered optimal in the soil.…”
Section: Discussionmentioning
confidence: 99%